A função dinâmica das partículas modais alemãs doch e ja no ensino de línguas - Marceli de Aquino Mateus (2012)
This research discusses the conversational and communicative functions of modal particles doch and ja in colloquial German language. The modal particle doch and ja, like many others, are not fully deciphered and understood by foreign students when translated, with only a few definitions, which often do not cover the complexity and the ability to completely change the intent of the speaker and, most importantly, the meaning of dialogue. The present research investigates translations of the aforementioned particles to Brazilian Portuguese; it also studies the importance of modal particles for the teaching of German language. To this end, four contemporary German movies were analyzed. The occurrences of the particles in these movies were submitted to the interpretation and translations of Brazilian German teachers and native German citizens that live in Brazil. This procedure provides a new point of view. Suitable translations proved strongly context dependent. Concerning to foreign language teaching, it was shown that modal particles must be constantly practiced in real situations and communication in order to make learning simultaneously dynamic and effective.